The antioxidant effects of pomegranate extract on local and remote organs in a mesenteric ischemia and reperfusion model - Kilic, Elif; TÜRKOĞLU, AHMET; Keles, Aysenur; Ekinci, Aysun; Kesgin, Siddika; Gumus, Metehan (My University, 2016)
Objectives: We investigated whether pomegranate extract plays a protective antioxidant role against mesenteric ischemia-reperfusion injury (IR), which can lead to a systemic response and damage distant organs, such as the lung, liver, and kidney. Methods: Forty female Wistar-Albino rats were separated into four groups: laparotomy, laparotomy + PG, mesenteric IR, and mesenteric IR and pomegranate (IR + PG). In the laparotomy + PG and IR + PG groups, pomegranate (225 mg/kg) was given by oral gavage at the beginning of the study. Ischemia was induced for 30 minutes, and reperfusion was subsequently allowed for 60 minutes in the IR and IR + PG groups. The malondialdehyde (MDA) and total antioxidant activity (AOA) levels were evaluated in blood samples. Additionally, all tissues were removed for the measurement of AOA and total oxidant status as well as for subsequent histopathological evaluation. The oxidative stress index was calculated. Results: Histopathological changes in all organs were significantly higher in the IR group and significantly lower in the IR + PG group vs. the other groups. Serum MDA levels were significantly lower in the IR + PG group than in the IR group. No significant difference was found in AOA levels of the groups. Discussion: These data may explain the positive protective effects of pomegranate based on the histopathologic findings in ischemic conditions in an intestinal IR injury model.
Keywords: Intestinal ischemia; Malondialdehyde; Pomegranate; Reperfusion